Integration of ESG Principles into the Sustainable Development Strategy of Kazakhstan - Lazat Spankulova; Assel Aben; Nurbakhyt Nurmukhametov; Saule Zeinolla (Journal of Central Asian Studies)
Kazakhstan is actively integrating Environmental, Social, and Governance (ESG) principles into its national sustainable development strategy. The implementation of ESG policies is considered a key driver of sustainable economic growth, enhancing investment attractiveness and improving the quality of life for the population. The purpose of the study is to identify key factors that contribute to the successful integration of ESG principles into the sustainable development strategy of Kazakhstan, as well as to identify the main barriers and opportunities on the path to carbon neutrality by 2060. The study highlights positive trends in Kazakhstan’s ESG policy, particularly in the transition to a green economy, supported by renewable energy investments and low-carbon policies, strengthened corporate governance standards and increased ESG reporting transparency, the role of state-led policies and international collaboration in driving ESG initiatives. This study employs a qualitative research approach, incorporating a literature review, case study analysis, and comparative assessment of ESG policies in Kazakhstan. It analyzes government regulations, corporate ESG reports, and international benchmarks to evaluate the country’s progress. A SWOT analysis is conducted to identify key strengths, weaknesses, opportunities, and threats in ESG implementation. The findings are based on data from global institutions (World Bank, OECD, UNDP), national policies, and corporate sustainability reports to provide a comprehensive evaluation.